COMPARISON OF ANTIMICROBIAL ACTIVITY OF TWO POLYMERIC GUANIDINE DERIVATIVES - Lysytsya, Andriy; Kryvoshyya, Pavlо (Collection of scientific papers «ΛΌГOΣ», 2023)
The polymeric guanidine derivatives have long proven to be efficient disinfectants and antiseptics. They have clearly expressed bactericidal, virucidal, fungicidal, and algicidal properties [1, 2]. There is much information on the application of polymeric guanidine derivatives in the composition of different disinfectants and antiseptics, for instance, e.g., in the treatment of hospital-acquired infections (biofilms) [2, 3, 4]. In addition, polyhexamethylene guanidine (PHMG), has also been used with some effect in the purification of sewage and underground waters [5].